The Effect of Giving Lemon Aromatherapy to Postpartum Mothers to Reduce Anxiety at TPMB (Midwife Independent Practice) E, Sukasari Village, Cilaku District, Cianjur Regency, Indonesia - Eka Ratnawati; Widia Natalia (HM Publisher, 2023)
The scent of lemon is known to improve mood and help reduce feelings of stress and anxiety. The fresh smell of lemon can have a refreshing and uplifting effect. Lemon aromatherapy can also help in creating a sense of relaxation and calm. This study aimed to determine the effect of giving lemon aromatherapy to postpartum mothers to reduce anxiety at TPMB (Midwife Independent Practice) E, Sukasari Village, Cilaku District, Cianjur Regency, Indonesia. This study is experimental research with a one group pre-post-test approach and uses primary data, namely measuring the degree of anxiety of post-partum mothers of research respondents. A total of 30 research subjects participated in this study, where the research subjects met the inclusion criteria. This study shows that the intervention of providing lemon aromatherapy is effective in reducing the level of anxiety in post-partum mothers. There was a decrease in the level of postpartum maternal anxiety after giving lemon aromatherapy and it was stated to be statistically different, p<0.05. In conclusion, there is an effect of giving lemon aromatherapy in reducing anxiety of postpartum mothers at TPMB (Midwife Independent Practice) E, Sukasari Village, Cilaku District, Cianjur Regency, Indonesia.